Daily consumption of pro-vitamin A biofortified (yellow) cassava improves serum retinol concentrations in preschool children in Nigeria: A randomized controlled trial - Afolami, Ibukun; Mwangi, Martin N.; Samuel, Folake; Boy, Erick; Ilona, Paul; Talsma, Elise F.; Feskens, Edith J. M.; Melse-Boonstra, Alida (American Society for Nutrition, 2021)
Background: Vitamin A deficiency is a public health problem in sub-Saharan Africa. Pro-vitamin A biofortified (yellow) cassava has the potential to contribute significantly to improve vitamin A status, especially in populations that are difficult to reach with other strategies. Objectives: The study aimed at determining the efficacy of biofortified cassava to improve vitamin A status of Nigerian preschool children. Methods: An open-label randomized controlled trial was conducted in southwestern Nigeria. In total, 176 preschool children (aged 3–5 y) were randomized into 2 parallel arms comprising an experimental group (n = 88), fed foods prepared from biofortified (yellow) cassava, and a control group (n = 88), fed foods prepared from white cassava, twice a day, 6 d a week for 93 d. Results: A total of 159 children completed the trial (yellow cassava group, n = 80; white cassava group, n = 79). Children consumed 221 and 74 µg/d retinol activity equivalents from intervention foods in the yellow and white cassava groups, respectively. The treatment effect on serum retinol concentrations at the end of the feeding trial was 0.06 µmol/L (95% CI: 0.004, 0.124 µmol/L), after adjustment for baseline retinol concentrations, inflammation, and asymptomatic malaria status. No significant treatment effects were detected for serum β-carotene (adjusted effect: 3.9%; 95% CI: −0.6%, 8.6%) and gut permeability (adjusted effect: 0.002; 95% CI: −0.089, 0.092), but a significant effect was detected for hemoglobin concentrations (adjusted effect: 3.08 g/L; 95% CI: 0.38, 5.78 g/L). Conclusions: Daily consumption of β-carotene from biofortified cassava improved serum retinol and hemoglobin concentrations modestly in Nigerian preschool children. This study was registered with clinicaltrials.gov as NCT02627222.